Regulatory experience in Peru II: the cases of electrical industry and drinking water - Fernández-Baca, Jorge (Universidad del Pacífico, 1998)
In this paper we analyze the regulatory experience in Peru for two public utilities. The first one is electricity, where most of the enterprises have been transferred to the private sector and there has been a remarkable quality improvement in the service provision. The second one is the water, a service sector that Peruvian Government has been reluctant to privatize, creating serious problems for an efficient management and the changes to improve the quality of the service.